Challenges and Strategic Solutions in Educational Resource Management in Underdeveloped Regions of Guangdong, China - Gui Simei; Syunu Trihantoyo; Ayu Wulandari (MASI Mandiri Edukasi, 2026)
Educational equity remains difficult to achieve in underdeveloped rural regions despite continuing policy efforts to reduce regional disparities in China. In Guangdong, previous studies have largely discussed rural education from macro-policy or economic perspectives, yet few have integrated resource allocation, teacher retention, governance, and digital empowerment into a single analytical framework. This study aims to examine the main challenges of educational resource management in underdeveloped regions of Guangdong and to propose strategic solutions for improving educational equity. A mixed-methods design was employed, combining a structured questionnaire administered across 30 rural schools with semi-structured interviews involving 10 key informants, including teachers, school administrators, and local education stakeholders. Quantitative data were analyzed using descriptive statistics, and qualitative data were analyzed using thematic analysis. The findings reveal four major challenges: unequal resource allocation, persistent teacher retention problems, limited effectiveness of local governance and policy implementation, and inadequate digital infrastructure. Among these, teacher retention emerged as the most critical issue, followed by resource inequality, while digital empowerment remained the weakest dimension. The study contributes an integrated framework for understanding rural educational inequality and offers practical implications for policy reform, teacher support, governance improvement, and digital investment in underdeveloped regions.